Implementasi File Server dan Sharing Printer Pada Kantor Desa Nunu Kecamatan Rainis Kabupaten Kepulauan Talaud - Eliyah Acantha M Sampetoding; Suryani Gumolung; Yulita Sirinti Pongtambing; Esther Sanda Manapa; Ikbal Tawinseet (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The era of globalization is one of the impacts of the development of information technology. The rapid development of technology and communication networks makes it easier for people to get information. Nunu Village is one of the villages in the Talaud Islands Regency on the border area of Indonesia and the Philippines. The research team made observations at the Village Office by conducting interviews with village heads and staff. The results of the observation focus on queuing in using computer or printer access. This happened because the data was stored on a certain computer and the printer was only connected to one computer in the Nunu Village Secretary's room. In Nunu Village, it is still done by sharing data from one computer to another manually, using external data storage devices such as flash drives and hard drives. Doing so can spread viruses and spyware that can damage computer data and operating systems. The initiative researcher conducts an online network system with implementation at the Village office